Shareholder Litigation and Conservative Accounting: Evidence from Universal Demand Laws - Manchiraju, Hariom; Pandey, Vivek; Subramanyam, K. R. (The Accounting Review, 2021)
ABSTRACT We use the staggered adoption of the Universal Demand Laws (UD Laws) to examine the effect of an exogenous reduction in shareholders' ability to litigate on the extent of accounting conservatism. On average, we find an increase in reporting conservatism post-UD. The increased conservatism is concentrated in firms that contemplate equity issuance, with a high proportion of monitoring investors, and high corporate governance quality. In contrast, firms with specific short-term incentives for aggressive accounting—such as those narrowly beating benchmarks, those with abnormal insider trading, and those likely to violate debt covenants—weakly governed firms, and firms with high ex ante litigation risk decrease reporting conservatism after UD. Our results suggest that the relation between the litigation environment and reporting conservatism is complex and dependent on specific characteristics and unique circumstances of the firms.